Hybrid discovery learning: Solutions for optimizing students' critical thinking and ICT skills on temperature fluctuations material - Sudi Dul Aji; Hena Dian Ayu; Mila Rosita; Cholisina Anik Prawira (Momentum: Physics Education Journal, 2024)
This research aims to optimize the critical thinking skills and information communication technology (ICT skills) of students regarding temperature fluctuations material through the implementation of a hybrid discovery learning method. The hybrid discovery learning method provides the efficacy and efficiency of the physics learning process at three Malang Junior High Schools. The type of research used was quasi-experimental with a post-test only group design. There were 143 students enrolled in this research, divided into six study groups. The experimental class consisted of 74 students, while the control class comprised 69 students. The data were collected using a multiple-choice test instrument that evaluated critical thinking skills at the cognitive level. The experimental group achieved an average score of 71.1, while the control group achieved 60.1. Furthermore, data pertaining to ICT skill was gathered through the utilization of observation sheet and questionnaires during the learning process. The Wilk’s Lambda in the Manova test gave results of Sig. (0,000) < (0,05). This demonstrates that the hybrid discovery learning model influences students' critical thinking and ICT skills. Therefore, the implementation of the hybrid discovery learning to temperature fluctuations material can optimize the learning process on the critical thinking and ICT skills.